2018
DOI: 10.1155/2018/8938307
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Anemia among Pregnant Women Attending Antenatal Clinic in Public Health Facilities at Durame Town: Unmatched Case Control Study

Abstract: Background Anemia among pregnant women is one of the most common public health problems in developing country. World health organization (WHO) estimate shows nearly half of pregnant women were affected by anemia. High burden of anemia is observed in Africa particularly in Ethiopia. However, the factors that contribute to the occurrence of anemia were not exhaustively studied. Therefore, the aim of this study was to identify determinant factors of anemia among pregnant women in Durame Town, southern Ethiopia. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
23
1
7

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(43 citation statements)
references
References 15 publications
12
23
1
7
Order By: Relevance
“…Multivitamins products, which contain vitamins and minerals including iron [37,38], are commonly consumed in China. The finding concerning meat intake was consistent with previous studies in Ethiopia [25,39,40], in which IDA was found more prevalent in regions with iron-poor diets such as central south, northwest, and east China [24,41].…”
Section: Supplementation and Screeningsupporting
confidence: 91%
“…Multivitamins products, which contain vitamins and minerals including iron [37,38], are commonly consumed in China. The finding concerning meat intake was consistent with previous studies in Ethiopia [25,39,40], in which IDA was found more prevalent in regions with iron-poor diets such as central south, northwest, and east China [24,41].…”
Section: Supplementation and Screeningsupporting
confidence: 91%
“…Women who had prolonged menstrual period before the index pregnancy were 2.7 times more likely to be anemic during pregnancy than who had less duration of menstruation (3-5 days), this result is in covenant with a study done in Mekelle City, 19 Dessie Hospital, 15 Yirgalem and Hawassa cities, 20 and in Durame town public health centers southern Ethiopia. 17 Persistent menstrual bleeding (> five days) was significantly related with the existence of severe anemia among pregnant mothers who came for ANC visits in Mekelle city public hospitals. 21 Mizantepi Teaching Hospital.…”
Section: Discussionmentioning
confidence: 96%
“…Despite this scientific fact, almost 46% of pregnant reported to have habit of drinking coffee or tea immediately after meal. Study done in Ethiopia showed that consuming tea/coffee immediately after food (AOR: 3.58) and not eating meat (AOR: 2.07) were associated with significant risk of anaemia [26]. This low awareness level in conjunction with low practice of three day meal, use of iron rich foods and low compliance to iron tablets (32%), it high likely that the study participants are at higher risks of anaemia.…”
Section: Open Access Freely Available Onlinementioning
confidence: 97%